Contribution of Tourism Products in Creating Satisfying Quality of Tourism Services and Tourist Loyalty - ROBUSTIN, Tri Palupi; SULARSO, Raden Andi; SUROSO, Imam; YULISETIARINI, Diah (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019, 2020)
This study aims to determine the effect of tourism product components consisting of attraction, facilities, and accessibility to satisfying quality of tourism services and tourist loyalty in the Regional Office of Jember East Java Province. Objects in the study were conducted at Papuma Beach in Jember Regency, Pulau Merah Beach in Banyuwangi Regency, and White Sand Beach in Situbondo Regency. The sampling technique used purposive sampling and accidental sampling with a sample of 102 respondents. The analytical tool used is path analysis (path analysis) using the help of SPSS Software. The results showed that the beach attractiveness variables and facilities had an influence on tourist loyalty variables both directly and indirectly through the variable Satisfying Quality of Tourism Services. Coastal attractiveness has the greatest indirect influence on tourist loyalty through Satisfying Quality of Tourism Services. This illustrates that the management of good coastal attractiveness in the tourism industry will encourage an increase in Satisfying Quality of Tourism Services which will ultimately encourage increased tourist loyalty. The results of the total influence were obtained that beach facilities had the greatest total influence on tourist loyalty. The results of this study contributed to the management of coastal tourism in the Regional Office of Jember, especially Papuma Beach in Jember Regency, Pulau Merah Beach in Banyuwangi Regency, and Pasir Putih Beach in Situbondo Regency, that the tourism industry should manage tourism product components in terms of maximum service quality, because it will have an impact on tourist satisfaction and loyalty.